2018
DOI: 10.3390/s18124107
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of High-Density EEG Signals in Stroke Patients

Abstract: Stroke is a critical event that causes the disruption of neural connections. There is increasing evidence that the brain tries to reorganize itself and to replace the damaged circuits, by establishing compensatory pathways. Intra- and extra-cellular currents are involved in the communication between neurons and the macroscopic effects of such currents can be detected at the scalp through electroencephalographic (EEG) sensors. EEG can be used to study the lesions in the brain indirectly, by studying their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In our case, we used a neurophysiologic method, such as HD-EEG, to obtain objective data and provide evidence of the importance and effectiveness of an intensive rehabilitative training in an aphasic patient. In fact, a study conducted on stroke patients with HD-EEG demonstrated that, with respect to standard EEG, high-density EEG could describe the asymmetric electrical signals of the brain activity in stroke patients [18]. Results showed that, during the repetition, reading and writing tasks, the left parieto-temporo-frontal areas are more activated at T1 respect to baseline evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…In our case, we used a neurophysiologic method, such as HD-EEG, to obtain objective data and provide evidence of the importance and effectiveness of an intensive rehabilitative training in an aphasic patient. In fact, a study conducted on stroke patients with HD-EEG demonstrated that, with respect to standard EEG, high-density EEG could describe the asymmetric electrical signals of the brain activity in stroke patients [18]. Results showed that, during the repetition, reading and writing tasks, the left parieto-temporo-frontal areas are more activated at T1 respect to baseline evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…From a neurological point of view, brain connections are weakened or completely lost because of the death of neurons. EEG is a powerful tool to explore brain functioning and detect any alterations in the presence of pathological conditions [43][44][45][46]. Recently, graph theory has widely been employed to quantify the brain functional connectivity; it has also been proved that brain networks are characterized by small-world architecture.…”
Section: Discussionmentioning
confidence: 99%
“…After some modifications it became the standard of the American Clinical Neurophysiology Society and the International Federation of Clinical Neurophysiology. Later, the results of several studies showed that the interelectrode distance should be between 1 cm and 3 cm, which implies the use of at least 100 electrodes [14][15][16][17][18][19]. Therefore, a farther extension of the 10-10 system was introduced, the so-called 10-5 system, which consists of 345 electrode locations [20] (Figure 2b).…”
Section: High-density Eegmentioning
confidence: 99%